1972
DOI: 10.2136/sssaj1972.03615995003600050023x
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Forms in Selected Temperate and Tropical Soils

Abstract: A scheme was developed for fractionating soil Mg into exchangeable, organic‐complexed, acid‐soluble, and primary mineral forms. The scheme was tried out on 20 soils from different regions of the world. Magnesium content was influenced by the nature of the parent materials, climate, and age of the soil. There was more Mg in youthful alluvial soils from Southeast Asia as well as loess and till‐derived Illinois soils which had high amounts of 2:1 lattice clays. Highly weathered oxisols from Sierra Leone were low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 0 publications
4
17
0
Order By: Relevance
“…Apparently the rate of release of non-exchangeable Mg is too low to adequately meet the crop requirements. With the clay fraction dominated by kaolinite, this is not unexpected (RICE and KAMPRATH, 1968;SALMON and ARNOLD, 1963;MOKWUNYE and MELSTED, 1972;CHRISTENSON and DOLL, 1913;LOMBIN and FAYEMI, 1916). From the evidence gathered from this study, it would seem that Mg deficiency in the Sudan and Sahel savannah zones of the country is already a reality.…”
Section: Magnesium Supplying Powers Of the Soils In Relation To Probamentioning
confidence: 90%
See 1 more Smart Citation
“…Apparently the rate of release of non-exchangeable Mg is too low to adequately meet the crop requirements. With the clay fraction dominated by kaolinite, this is not unexpected (RICE and KAMPRATH, 1968;SALMON and ARNOLD, 1963;MOKWUNYE and MELSTED, 1972;CHRISTENSON and DOLL, 1913;LOMBIN and FAYEMI, 1916). From the evidence gathered from this study, it would seem that Mg deficiency in the Sudan and Sahel savannah zones of the country is already a reality.…”
Section: Magnesium Supplying Powers Of the Soils In Relation To Probamentioning
confidence: 90%
“…The total Mg content of a soil is a product of its parent materials, state of maturity and the bio-climatic forces in operation (MOKWUNYE and MELSTED, 1972). Among the factors that govern its availability to plants are the total quantity present in the soils, level of soil organic matter (ILEY, 1969) the quantum and quality of the clay fraction (RICE and KAMPRATH, 1968; soil reaction, (ADAMS and HENDERSON 1962; exchangeable cation ratios (DOLL and HOSSNER, 1964;MCCOLLUCH et al, 1957).…”
mentioning
confidence: 99%
“…Mokwunye and Melsted (1972) found that highly weathered soils contained much less total Mg than less weathered soils. A similar pattern was found for the Fiji soils studied.…”
Section: Total Magnesiummentioning
confidence: 97%
“…This represents the Mg present in nonexchangeable forms associated with silicate clays most probably in the interlayers of chlorites and vermiculites (Baker 1972). Literature values of acid-soluble Mg ranged from 2.5 to more than 500 mmol/kg (Mokwunye and Melsted 1972;Metson 1974). The Fiji soils gave contents of acidsoluble Mg ranging from 13 to 478 mmol/kg constituting 2-60% of total Mg.…”
Section: Acid-soluble Magnesiummentioning
confidence: 99%
See 1 more Smart Citation